A chiral BINOL-based Gemini amphiphilic gelator and its specific discrimination of native arginine by gelation in water. Issue 32 (17th July 2017) - Jia, Lihua; Yin, Jianxin; Guo, Xiangfeng; Cao, Guangzhou; Tian, Xuhua; Zhu, Bo; Pu, Lin
Abstract : A novel axially chiral cationic Gemini amphiphile gelator (S1 ) derived from (S )-BINOL has been synthesized and characterized by 1 H NMR, 13 C NMR, ESI-MS and FT-IR analyses. Abstract : A novel axially chiral cationic Gemini amphiphile gelator (S1 ) derived from (S )-BINOL has been synthesized and characterized by 1 H NMR, 13 C NMR, ESI-MS and FT-IR analyses. The critical micelle concentration (CMC) ofS1 was determined to be 0.21 mM in water at room temperature. A transparent hydrogel withS1 at 43 mM was obtained at room temperature and characterized using various methods including SEM, CD, fluorescence, 1 H NMR, FT-IR, and XRD. The results indicate that the hydrophobic effect of long alkyl chains, π–π stacking of naphthalene rings, and intermolecular hydrogen-bonding of the amide groups ofS1 should be responsible for the hydrogel formation. Moreover, an 8.5 mM aqueous solution ofS1 could gel by the addition ofl -arginine, whereas it failed to gel in the presence of other 15 amino acids, respectively. It is suggested thatS1 could discriminate native arginine by hydrogel formation, mainly due to the electrostatic interaction and hydrogen bonding effects betweenS1 andl -arginine molecules.